Economic shocks and children’s dropout from primary school: Implications for education policy in Ethiopia - Woldehanna, T; Hagos, A (Taylor and Francis, 2015)
This paper investigates the impact of idiosyncratic and covariate economic shocks, on the likelihood of children dropping out of primary school. In this endeavour, an Accelerated Failure Time Hazard model was estimated using data from the Young Lives study of childhood poverty. The estimated results indicate that both idiosyncratic shocks and covariate shocks have a statistically significant effect on the risk of children dropping out of primary school. Considering the fact that both idiosyncratic and area-wide economic shocks are experienced at the household level, the study concludes that it is vital to link social protection programmes to education policy as well so as to reduce the vulnerability of households to the shocks and keep children from dropping out from school.